THE POTENTIAL EFFECT OF APORPHINE ALKALOIDS FROM NELUMBO NUCIFERA GAERTN. AS ANTI-BREAST CANCER BASED ON NETWORK PHARMACOLOGY AND MOLECULAR DOCKING - ADRIAN; LUBIS, MUHAMMAD FAUZAN; SYAHPUTRA, RONY ABDI; ASTYKA, RIRIN; SUMAIYAH, SUMAIYAH; YUDHA HARAHAP, MUHAMMAD ANDIKA; AINI, ZAHRATUL (International Journal of Applied Pharmaceutics, 2024)
Objective: To demonstrate the efficacy and benefits of aporphine alkaloids from Nelumbo nucifera Gaertn. as anti-breast cancer agents. Methods: In this study, a combination of network pharmacology and molecular docking was used to investigate the pharmacological actions and underlying mechanisms of action of nuciferine, nor-nuciferine, and roemerine against breast cancer. Results: Fifty-five potential targets of compounds against breast cancer were identified. The Epidermal Growth Factor Receptor (EGFR), Mitogen-Activated Protein Kinase 8 (MAPK8), Janus Kinase 2 (JAK2), Inhibitor of Nuclear Factor Kappa B Kinase Subunit Beta (IKBKB), and Protein Kinase C Epsilon (PRKCE) were identified as the top five targets of compounds against breast cancer. Molecular docking demonstrated that these compounds could bind spontaneously to the screened top 4 targeted proteins. Conclusion: The present study demonstrates that these compounds have pharmacological effects against breast cancer via a multi-target and multi-pathway manner.